Models for CIE color parameter differentials of pasteurized citrus microcarpa juices - Alagao, Ma. Estela Elanor V. (2007)
ABSTRACT This study was conducted to establish mathematical models for the prediction of changes in color characteristics of thermally processed Citrus microcarpa juice as a function of pasteurization time and temperature. The ΔL*, Δa* and Δb* values from the color analyses were fitted into second order models. Results of the regression ANOVA showed that the models can reliably predict the ΔL*, Δa* and Δb* of pasteurized juice. All individual and interactive predictive parameters were significantly (p<0.05) associated with ΔL* of calamansi juice. The quadratic effect of temperature as well as the interactive effect of time and temperature were not significantly associated with Δa* of calamansi juice while the rest of the parameters were significantly associated to Δb.